Application of Descriptive and Inferential Statistics in Guidance and Counseling Research - Rober Sandra; Daharnis; Rezki Hariko (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study aims to examine the role and application of descriptive and inferential statistics in guidance and counseling research. Descriptive statistics are employed to present data characteristics such as perceptions, attitudes, and satisfaction levels toward counseling services, while inferential statistics are used to test hypotheses, explore relationships between variables, and assess the effectiveness of counseling programs. This qualitative review analyzed 15 relevant international journal articles. The findings indicate that the use of statistics in counseling research not only enhances the validity and reliability of findings but also aids school counselors in making data-driven decisions. The study recommends improving statistical literacy among guidance and counseling practitioners and researchers as a crucial step toward strengthening evidence-based practices.